Is there a link between upper gastrointestinal polyps and colonic polyps? A retrospective study from a Turkish cohort - Sozen,Meral (2016)
OBJECTIVE: To investigate the incidence and associated demographical and clinical factors related to lower GI polyps and neoplasms in patients with upper GI polyps and neoplasms. METHODS: We investigated 99 patients who had upper GI polyps and neoplasms and who were screened with colonoscopy: the following data were collected: demographical and clinical data consisting of age, sex, smoking status, presence of H. pylori infection, placement of upper GI polyps or neoplasms, presence of gastric atrophy, usage of proton pump inhibitors (PPI), presence of lower GI polyp or neoplasm, type of colon polyp, pathological grade of colon polyp. The patients were grouped according to having/not having lower GI polyps and neoplasms; data was compared between groups. RESULTS: Smoking rate was significantly higher in patients with lower GI polyps and neoplasms (χ2: 4.35, p: 0.03). Furthermore, there was a signifant association between presence of lower GI polyps and neoplasms vs. smoking (OR: 2.44 CI: 1.01-5.84, p: 0.04). CONCLUSIONS: Patients with upper GI polyps and neoplasms who are smokers should be considered as candidates for having lower GI polyps and neoplasms and should be screened and followed more carefully. Additionally, we believe that large sampled and prospective studies are needed to higligt the association between upper GI polyps and presence of lower GI polyps and neoplasms.